Positive Selection of Deleterious Alleles through Interaction with a Sex-Ratio Suppressor Gene in African Buffalo: A Plausible New Mechanism for a High Frequency Anomaly - van Hooft, Pim; Greyling, Ben J.; Getz, Wayne M.; van Helden, Paul D.; Zwaan, Bas J.; Bastos, Armanda D. S. (PLOS ONE, 2014)
Although generally rare, deleterious alleles can become common through genetic drift, hitchhiking or reductions in selective constraints. Here we present a possible new mechanism that explains the attainment of high frequencies of deleterious alleles in the African buffalo (Syncerus caffer) population of Kruger National Park, through positive selection of these alleles that is ultimately driven by a sex-ratio suppressor. We have previously shown that one in four Kruger buffalo has a Y-chromosome profile that, despite being associated with low body condition, appears to impart a relative reproductive advantage, and which is stably maintained through a sex-ratio suppressor. Apparently, this sex-ratio suppressor prevents fertility reduction that generally accompanies sex-ratio distortion. We hypothesize that this body-condition-associated reproductive advantage increases the fitness of alleles that negatively affect male body condition, causing genome-wide positive selection of these alleles. To investigate this we genotyped 459 buffalo using 17 autosomal microsatellites. By correlating heterozygosity with body condition (heterozygosity-fitness correlations), we found that most microsatellites were associated with one of two gene types: one with elevated frequencies of deleterious alleles that have a negative effect on body condition, irrespective of sex; the other with elevated frequencies of sexually antagonistic alleles that are negative for male body condition but positive for female body condition. Positive selection and a direct association with a Y-chromosomal sex-ratio suppressor are indicated, respectively, by allele clines and by relatively high numbers of homozygous deleterious alleles among sex-ratio suppressor carriers. This study, which employs novel statistical techniques to analyse heterozygosity-fitness correlations, is the first to demonstrate the abundance of sexually-antagonistic genes in a natural mammal population. It also has important implications for our understanding not only of the evolutionary and ecological dynamics of sex-ratio distorters and suppressors, but also of the functioning of deleterious and sexually-antagonistic alleles, and their impact on population viability.